The Evaluation of Palasari Reservoir Water Balance for Palasari Irrigation Area by Using RIBASIM - Lelyana, Novia; Arsana, I Gusti Ngurah Kerta; Pariartha, I Putu Gustave Suryantara (Universitas Ibn Khaldun Bogor, 2026)
One of the attempts to manage water resources is to build dams. One of the large dams in Indonesia, the Palasari Dam, which is located in Bali Province, was built in 1987 - 1989. The utilization purpose of the Palasari Dam is to irrigate the planned Palasari Irrigation Area in the amount of 1,300 Ha. However, the Palasari Reservoir challenges sedimentation and a lowering of storage water level, especially during the drought. This condition inflicts disruption of water availability. In the face of scarcity of water resources, it is necessary to explore water availability for efficient and effective distribution. In optimizing reservoirs, operational simulation analysis to determine the reliability of reservoir operations can use RIBASIM (River Basin Simulation) software by evaluating the results of the composition and distribution of water discharge. This research aims to evaluate the irrigation inflow released by the operation of the Palasari Reservoir to serve the Palasari Irrigation Area. Calculations for irrigation water demand in the Palasari Irrigation Area were carried out by the existing global crop plan, as well as modeling simulations with six rice field plots that were irrigated directly by the Palasari Reservoir using RIBASIM. Based on the results of model simulations, the existing discharge cannot fulfill water demands in the Palasari Irrigation Area. Hereafter, with the simulated annual average irrigation water demand of the Palasari Irrigation Area of 9.915 Mcm (0.314 m3/s), it still runs into a water shortage of 4.049 Mcm (0.128 m3/s) with a shortage rate of 40.76%.